Sebacious horn that developed in the surgical scar - Lakhey, Rajesh Vahadur; Adhikari, Sharad Chandra; Kafle, Dinesh (Journal of Chitwan Medical College, 2021)
Sebaceous horns are rare lesions that occur as conical projections in sun-exposed parts of the body. They are made of hyperkeratotic material and look like horns of the animals. They may harbor benign, premalignant, and malignant lesions at their bases. We present a case of a 49-year-old lady who presented with a conical growth at the operative scar of minimally invasive open lumbar discectomy. Excision of the horn along with the base was done, and the histopathology revealed benign seborrheic keratosis, suggesting sebaceous horn.